2004
DOI: 10.1191/1463423604pc224oa
|View full text |Cite
|
Sign up to set email alerts
|

Developing public health work in local health systems

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…As this research has illustrated, social problems are often complex, and responding to them can be a frustrating experience for GPs. Related research has found that community nurses also feel frustrated by their attempts to respond to the social causes of ill health, feeling that this work is not valued and receiving little support at an organisational level 39 42. It appears that primary care practitioners invest a considerable amount of time with patients experiencing social problems, so improving their referral options could save professional time, make their work more satisfying and address the social causes of health inequalities more effectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As this research has illustrated, social problems are often complex, and responding to them can be a frustrating experience for GPs. Related research has found that community nurses also feel frustrated by their attempts to respond to the social causes of ill health, feeling that this work is not valued and receiving little support at an organisational level 39 42. It appears that primary care practitioners invest a considerable amount of time with patients experiencing social problems, so improving their referral options could save professional time, make their work more satisfying and address the social causes of health inequalities more effectively.…”
Section: Discussionmentioning
confidence: 99%
“…The research was part of a larger programme of work on the relationship between public health and primary care in two local health systems in England 12 3739. The study reported on in parts 1 and 2 of this paper focused on the pathways people follow as they seek help to manage the social problems associated with health inequalities and to consider, in particular, the role of general practice and primary care in these pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Interview transcripts were read extensively and a thematic index (of the overarching concepts of definition of fall, establishing a cause, instinct, environment, physical issues, mobility, willingness to go to hospital, other professionals, social aspects and miscellaneous) developed after discussion between two researchers. Two transcripts were independently indexed by two researchers and then compared to ensure transparency 17. Summaries and direct quotes from the transcripts were placed into a table depicting the thematic index.…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, for example, general practice in the UK has resisted becoming involved in public health practice focusing on the wider social causes of ill health, and multidisciplinary working faces many barriers 1517. There has been relatively little in the way of experimentation with social models of primary care, such as the Community Oriented Primary Care model developed in other countries 7.…”
Section: Discussionmentioning
confidence: 99%